Movement behaviour education for parents in prenatal, postnatal, and pediatric care in Canada: A needs assessment - Brianne A. Bruijns; Matthew Bourke; Aidan Loh; Patricia Tucker (BMC, 2024)
Abstract Background Parents/guardians can greatly influence their child's movement behaviours (i.e., physical activity, sedentary behaviour, and sleep). Yet, they have reported to lack sufficient background knowledge to foster healthy movement habits, and little is known about specific educational gaps. The aim of this study was to explore the educational background and needs regarding promoting healthy movement behaviours in early childhood among parents/guardians living in Canada. Methods A cross-sectional study was conducted with parents/guardians living in Canada who had at least one child under the age of 5 years. Participants completed an online survey capturing their demographics, information they received about movement behaviours in early childhood during their prenatal/postnatal care or child's pediatrician appointments, where they sourced information about these topics, content areas they would like more information on, and preferred format for delivery. Descriptive statistics and frequencies were calculated for all outcome variables and logistic regression was used to explore if sociodemographic variables were associated with receiving movement behaviour-related education across care types. Results Among the 576 parents/guardians who completed the survey, many reported no mention of any movement behaviour in their prenatal (49.4%), postnatal (29.6%), and pediatric care (37.2%). Physical activity was the most cited movement behaviour across care types, with 42.4%, 57.9%, and 54.8% of participants indicating this was discussed in their prenatal, postnatal, and pediatric care, respectively. Only 41.7% of parents/guardians reported asking their child's pediatrician about movement behaviours, while most relied on social media (70.9%), internet websites/news articles (68.7%), and family/friends (67.6%). The most sought-after movement behaviour topics included incorporating movement into traditionally sedentary activities (68.8%) and activity ideas to break up sitting time (65.0%), and participants expressed preference to receive more information via social media (63.2%), an online resource package (47.8%), or email (46.6%). Conclusions Given the noted inconsistencies in education relating to movement behaviours in maternal and pediatric care, this study highlights the opportunity for greater integration of this type of education across care types. Ensuring all parents/guardians receive evidence-based and consistent guidance on their child's movement behaviours will help ensure young children receive the best start to a healthy active life.